A High Return Loss of Microwave Bandpass Filter Using Superconducting Electrospun YBCO Nanostructures - Jasim, S. E.; M. A., Jusoh; Yeow, Y. K.; Rajan, Jose (EMW Publishing, 2018)
A high return loss (-30 dB), small size (100 mm2) and broad bandwidth (1.5 GHz) microwave bandpass filter has been designed using finite element modelling and developed using the superconducting YBa2Cu3O7-δ (YBCO) thin films deposited on a (10 × 10 mm2) LaAlO3 substrate by spin coating. The thin films have been prepared by electrospinning and solid-state techniques. The microwave properties of filter circuits were experimentally determined using the vector network analyser (VNA) at room temperature (300 K) and in the presence of liquid nitrogen (77 K). The solid-state filter showed high return loss (i.e. -22 dB) at operating frequency of 9.7 GHz and broad bandwidth of 1.5 GHz, which is consistent with the simulation results. The insertion losses for YBCO filters are ~-2, ~-1.5 and ~-3 dB for the normal, nanoparticle and nanorod respectively. However, the electrospun filters exhibited lower performance due to the nano-structural properties of YBCO samples at nanoscale which make these sample have a large band gap compared to solid-state sample. The results indicate that the filter design and simulation result are reliable. Hence, HTS YBCO could be a potential microwave bandpass filter in industry.